Measurement of Human Semicircular Canal Spatial Attitude - Wu, Shuzhi; Lin, Ping; Zheng, Yanyan; Zhou, Yifei; Liu, Zhaobang; Yang, Xiaokai (Frontiers in Neurology, 2021)
Located deep in the temporal bone, the semicircular canal is a subtle structure that requires a spatial coordinate system for measurement and observation. In this study, fifty-five semicircular canal and eyeball models were obtained by segmentation of MRI data. The spatial coordinate system was established by taking the top of the common crus and the bottom of the eyeball as the horizontal plane. First, the plane equation was established according to the centerline of the semicircular canals. Then, according to the parameters of the plane equation, the plane normal vectors were obtained. Finally, the average unit normal vector of each semicircular canal plane was obtained by calculating the average value of the vectors. The standard normal vectors of the right and left posterior semicircular canal, superior semicircular canal and lateral semicircular canal were [-0.651, 0.702, 0.287], [0.749, 0.577, 0.324], [-0.017, -0.299, 0.954], [0.660, 0.702, 0.266], [-0.739, 0.588, 0.329], [0.025, -0.279, 0.960]. The different angles for the different ways of calculating the standard normal vectors of the right and left posterior semicircular canal, superior semicircular canal and lateral semicircular canal were 0.011, 0.028, 0.008, 0.011, 0.024, and 0.006 degrees. The technology for measuring the semicircular canal spatial attitudes in this study are reliable, and the measurement results can guide vestibular function examinations and help with guiding the diagnosis and treatment of BPPV.